Role of inducible nitric oxide synthase in asthma risk and lung function growth during adolescence. Issue 2 (8th December 2009) - Islam, Talat; Breton, Carrie; Salam, Muhammad T; McConnell, Rob; Wenten, Made; Gauderman, W James; Conti, David; Van Den Berg, David; Peters, John M; Gilliland, Frank D
Abstract : Background: Inducible nitric oxide (NO) synthase (iNOS, encoded by NOS2A ) produces NO in response to environmental stimuli, which can result in nitrosative stress. Because nitrosative stress affects respiratory health, it was hypothesised that variants in NOS2A are associated with asthma incidence and lung function growth during adolescence. Methods: In this prospective study, spirometric testing was performed at school and a presence or absence of asthma was ascertained annually by questionnaire among children participating in the Southern California Children's Health Study. 24 single nucleotide polymorphisms (SNPs) of the NOS2A region (with seven promoter SNPs in one haplotype block), spanning 20 kb upstream and 10 kb downstream were genotyped. Association between the NOS2A region and asthma or lung function growth was tested using genetic block-specific principal component and haplotype analyses. This study was restricted to children with Latino and Caucasian ancestry for analyses of both asthma (n=1596) and lung function growth (n=2108). Result: A pair of "yin–yang" haplotypes in the promoter region showed strong association with new-onset asthma and lung function growth. The "yin" haplotype (h0111101) was associated with 44% increased asthma risk (p=0.003) and reduced forced expiratory volume in 1 s (FEV1 ) growth from 10 to 18 years of age (−29.46 ml, p=0.07), whereas the "yang"(h1000010) haplotype was associated with 23% reduced asthma risk (p=0.13) and better FEV1 growth (43.84 ml, p=0.01). Furthermore, the increased asthma risk associated with h0111101 was restricted to children with the GSTM1 "null" genotype (interaction p=0.002, HR 1.89, 95% CI 1.34 to 2.60). Conclusion: Common haplotypes in the NOS2A promoter are associated with new-onset asthma and lung function growth. These effects are stronger in adolescents with the GSTM1 "null" genotype.